Mitigation of the salinity stress in rapeseed (Brassica napus L.) productivity by exogenous applications of bio-selenium nanoparticles during the early seedling stage. (1st October 2022) - El-Badri, Ali Mahmoud; Batool, Maria; Mohamed, Ibrahim A.A.; Wang, Zongkai; Wang, Chunyun; Tabl, Karim M.; Khatab, Ahmed; Kuai, Jie; Wang, Jing; Wang, Bo; Zhou, Guangsheng
Abstract: In recent years, much attention has been directed toward using nanoparticles (NPs) as one of the most effective strategies to improve plant growth, especially under salt stress conditions. Further research has been conducted to develop NPs using various chemical ways; accordingly, knowledge about the beneficial effect of bioSeNPs in rapeseed is obscure. Selenium (Se) is a vital micronutrient with a series of physiological and antioxidative properties. Seed priming is emerging as a low-cost, efficient, and environment-friendly seed treatment in nanotechnology. The current study was carried out to examine the promising effects of nanopriming via bioSeNPs on the expression level of aquaporin genes, seed microstructure, seed germination, growth traits, physiochemical attributes, and minerals uptake of two rapeseed cultivars under salinity stress conditions. Our investigation monitored the positive effects of bioSeNPs on the expression level of aquaporin genes (BnPIP1-1 and BnPIP2-1 ) and water uptake during the seed imbibition (4 and 8 h of priming), which indicated higher imbibition potential and germination promotion with bioSeNPs application (most effective at 150 μmol/L). The total performance index was significantly enhanced with nano-treatments in rapeseed seedlings. Collectively, nano-application improved seed microstructure, seed germination, and photosynthetic efficiency directly correlated with higher seedlings biomass, especially with a higher concentration of bioSeNPs. The enhancement in α- amylase and free amino acid contents in nanoprimed seeds resulted in rapid seed germination. Moreover, bioSeNPs increased the osmotic adjustment and enhanced the efficiency of the plant's defense system by improving the activity of enzymatic and non-enzymatic antioxidants, thus enhancing ROS scavenging under salt stress. The obtained results may indicate the strengthening of seed vigor, improving seedling growth and physiochemical attributes via bioSeNPs. Our findings displayed that bioSeNPs modulated the Na + and K + uptake, which improved the rapeseed growth and showed a close relationship with the low contents of toxic Na + ion; thus, it prevented oxidative damage due to salt stress. This comprehensive data can add more knowledge to understand the mechanisms behind plant-bioSeNPs interaction and provide physiological evidence for the beneficial roles of nanopriming using bioSeNPs on rapeseed germination and seedling development under salinity stress conditions. Such studies can be used to develop simple prepackaged nano primer products, which can be used before sowing to boost seed germination and crop productivity under stress conditions.